Natrelle Silicone Breast Implant Follow-Up Study: Demographics, Lifestyle, and Surgical Characteristics of More Than 50,000 Augmentation Subjects - Singh, Navin; Picha, George J; Murphy, Diane K (Plastic and reconstructive surgery (1963), 2016)
A large, multicenter, 10-year observational study is being conducted to compare the long-term safety and effectiveness of Natrelle silicone breast implants with saline implants or national norms. Study baseline data and surgical characteristics are reported here. Women seeking primary augmentation, revision-augmentation, primary reconstruction, or revision-reconstruction participated. Eligible subjects had completed surgery and received one implant or matching implants. Baseline demographics, health, lifestyle, and surgical characteristics were recorded. Data are presented here for subjects (≥22 years old) who underwent primary augmentation or revision-augmentation. Of 50,979 subjects who underwent augmentation procedures, 35,756 received silicone implants and 15,223 received saline implants. Of these, 86.3 percent underwent primary augmentation, and 13.7 percent underwent revision-augmentation; nearly all subjects (99.3 percent) received bilateral implants. In the primary augmentation group, 67.6 percent of subjects received silicone implants versus 86.1 percent in the revision-augmentation group. Median age was lower in the primary augmentation group compared with the revision-augmentation group (33 versus 42 years old, respectively). Most subjects were white nonsmokers and had attended college. Hispanic subjects and subjects with a body mass index of 25 kg/m or greater were more likely to receive saline versus silicone implants. Across groups, the most common characteristics by procedure or implant type included inframammary incision site (54.6 percent), partial (58.2 percent) or complete (31.9 percent) submuscular placement, smooth surface implants (93.1 percent), and implant size of 300 to 399 cc. Incision size was larger for silicone versus saline implants. These data add to the body of knowledge on women undergoing augmentation procedures by providing an unprecedented look at a large number of subjects.